Evaluating The Impact of Mexico's Quality Schools Program : The Pitfalls of Using Nonexperimental Data - Skoufias, Emmanuel (The World Bank, 2006)
The authors evaluate whether increasing school resources and decentralizing management decisions at the school level improves learning in a developing country. Mexico's Quality Schools Program (PEC), following many other countries and U.S. states, offers US